Selection of Exposure Parameters for a HIFU Ablation System Using an Array of Thermocouples and Numerical Simulations - FURA, Łukasz; KUJAWSKA, Tamara (Archives of Acoustics, 2019)
Image-guided High Intensity Focused Ultrasound (HIFU) technique is dynamically developing technology for treating solid tumors due to its non-invasive nature. Before a HIFU ablation system is ready for use, the exposure parameters of the HIFU beam capable of destroying the treated tissue without damaging the surrounding tissues should be selected to ensure the safety of therapy. The purpose of this work was to select the threshold acoustic power as well as the step and rate of movement of the HIFU beam, generated by a transducer intended to be used in the HIFU ablation system being developed, by using an array of thermocouples and numerical simulations. For experiments a bowl-shaped 64-mm, 1.05 MHz HIFU transducer with a 62.6 mm focal length (f-number 0.98) generated pulsed waves propagating in two-layer media: water/ex vivo pork loin tissue (50 mm/40 mm) was used. To determine a threshold power of the HIFU beam capable of creating the necrotic lesion in a small volume within the tested tissue during less than 3 s each tissue sample was sonicated by multiple parallel HIFU beams of different acoustic power focused at a depth of 12.6 mm below the tissue surface. Location of the maximum heating as well as the relaxation time of the tested tissue were determined from temperature variations recorded during and after sonication by five thermo-couples placed along the acoustic axis of each HIFU beam as well as from numerical simulations. The obtained results enabled to assess the location of each necrotic lesion as well as to determine the step and rate of the HIFU beam movement. The location and extent of the necrotic lesions created was verified using ultrasound images of tissue after sonication and visual inspection after cutting the samples. The threshold acoustic power of the HIFU beam capable of creating the local necrotic lesion in the tested tissue within 3 s without damaging of surrounding tissues was found to be 24 W, and the pause between sonications was found to be more than 40 s. (f-number 0.98) and propagated in two-layer media: water/ex vivo pork loin tissue (50mm/40mm). The thickness of a water layer was determined from a nonlinear propagation model. To determine a threshold power of the HIFU beam capable of creating a necrotic lesion in small volume within a tested tissue during exposure less than 3s the tissue samples were sonicated by parallel HIFU beams with a varied acoustic power (8W - 36W) focused at a depth of 12.6 mm below the tissue surface. The location of the maximum heating spot induced by these beams as well as the tissue relaxation time were determined from temperatures recorded by a thermocouple array placed on the acoustic axis of each HIFU beam. The results obtained enabled to detect the location of necrotic lesions as well as the scanning speed of the tumor by means of the HIFU beam focus. The location of necrotic lesions was verified by ultrasonic images of tissue samples after their sonication and by visual inspection of visible lesions after cutting the samples. Results of the experiments showed that the threshold acoustic power of the HIFU beam capable of creating local necrotic lesion in the ex vivo pork loin tissue within 3s without damaging of surrounding tissue structures amounted to 24 W, and the interval between exposures, resulting from the relaxation time of tissue, was above 40 seconds.